A Case of Lower-Pole Moiety Ureteral Stenosis Close to Ureteropelvic Junction in an Incomplete Duplicated Collecting System Managed by Retrograde Balloon Dilatation that Needed a 2nd Ureteral Stent to the Upper-Pole - Seiichi Saito (Case Reports in Urology)
A 71-year-old woman presented at our institution with the chief complaints of left back pain and fatigue. Radiographic examination revealed left ureteral stenosis close to ureteropelvic junction of the lower-pole with a left incomplete duplicated collecting system. Transurethral retrograde balloon dilatation under general anesthesia was performed, and a ureteral stent was inserted to the lower-pole; however, there was urinary leakage from the upper-pole at the dilated ureteral stenosis lesion, and therefore, another ureteral stent was inserted to the upper-pole just after the first stent insertion. Both stents were removed at 6 weeks and subsequent intravenous pyelography confirmed resolution of the obstruction. The patient has remained asymptomatic during 2 years of follow-up.